Proceedings of XIII Nuclei in the Cosmos — PoS(NIC XIII) 2015
DOI: 10.22323/1.204.0073
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosynthesis of Mo in neutrino-driven winds

Abstract: Neutrino-driven winds that follow core-collapse supernovae are an exciting astrophysical site for the production of heavy elements. Although hydrodynamical simulations show that the conditions in the wind are not extreme enough for a r-process up to uranium, neutrino-driven winds may be the astrophysical site where lighter heavy elements between Sr an Ag are produced, either by the weak r-process or by the νp-process. However, it is still not clear if the conditions in the wind are slightly neutron-rich or pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It has been shown that different astrophysical sites provide favourable conditions for the production of these isotopes: in (single-degenerate) SNe Ia a γ-process can operate, photodissociating seed nuclei previously produced by the s-process in the companion star [83,84,20]. Neutrino-driven winds in CCSNe have also been studied extensively, with Hoffman et al [22] showing that neutron-rich conditions can lead to the production of the 92,94 Mo isotopes and Bliss & Arcones [71] showing that this is not possible for 96,98 Ru and that the solar ratio between the two Mo isotopes could not be achieved under any conditions. However, the observed solar abundance ratios cannot be achieved in either of the proposed scenarios.…”
Section: The Road To Solar Isotopic Mo and Ru Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that different astrophysical sites provide favourable conditions for the production of these isotopes: in (single-degenerate) SNe Ia a γ-process can operate, photodissociating seed nuclei previously produced by the s-process in the companion star [83,84,20]. Neutrino-driven winds in CCSNe have also been studied extensively, with Hoffman et al [22] showing that neutron-rich conditions can lead to the production of the 92,94 Mo isotopes and Bliss & Arcones [71] showing that this is not possible for 96,98 Ru and that the solar ratio between the two Mo isotopes could not be achieved under any conditions. However, the observed solar abundance ratios cannot be achieved in either of the proposed scenarios.…”
Section: The Road To Solar Isotopic Mo and Ru Ratiosmentioning
confidence: 99%
“…In the search of the origin of the solar 92,94 Mo and 96,98 Ru abundances, slightly neutron-rich conditions in neutrino-driven winds of CCSNe have been considered before [14,22,[70][71][72]. It is of particular interest to understand the conditions that lead to large abundances for these isotopes.…”
Section: < mentioning
confidence: 99%
“…The aim is to reproduce the observed abundances by one or more astrophysical scenarios and to determine their contribution to the galactical chemical evolution. Proton-rich neutrino-wind components like the νp process are unable to reproduce the 92,94 Mo solar isotopic ratio [40,41]. Therefore, they do not play a dominant role in the production of the solar inventory of these species.…”
Section: The Origin Of the P Nucleimentioning
confidence: 99%
“…[113] proposed that such anomalies are compatible with nucleosynthesis signatures from neutrino-driven winds from CCSNe. This scenario might also explain other anomalies in Mo, e.g., the 95,97 Mo excess compared to solar abundances [113,41]. However, also silicon carbide grains require to condense in C-rich material [94], and isotopic signatures for light elements seem to be compatible with C-rich material from explosive He burning regions [114,88] and not with O-rich material [115].…”
Section: Anomalies In Meteoritesmentioning
confidence: 99%
“…Alternative scenarios to explain neutron-capture signatures in Mo and in all other elements measured in SiC X grains include the neutrino-wind components from the forming neutron star as a source (Hallmann et al 2013, Bliss & Arcones 2014. In this work, we will instead consider the most established scenario to explain the Mo isotopic signature, i.e., where the neutron burst triggered by the 22 Ne(α,n) 25 Mg reaction is the responsible source.…”
Section: Introductionmentioning
confidence: 99%